PERANCANGAN SISTEM INFORMASI PROFIL SEKOLAH BERBASIS WEB MENGGUNAKAN METODE WATERFALL - Asmat; Rahmat Adnan Fauzan; Rinawang Tyas Arinanto; Saprudin (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
Information systems are widely used in an institution. For example in a company, office and education. In educational institutions information systems This aims to promote or provide an overview of the institution's profile related education, administration, and other facilities, Vocational High School ALMUHTADIN VOCATIONAL SCHOOL, Depok City, is one of the schools in the Cipayung sub-district, Dalam providing school information is still done manually, namely the school socialize and interact with the wider community such as school profiles, student data, teacher data, and class schedule information. This study aims to design a system web-based school profile information at SMK AL-MUHTADIN Depok City. Data used is secondary data in the form of documents obtained directly from SMK AL-MUHTADIN Depok City. This system uses HTML, PHP, CSS and MySQL programming languages as the database. This system is expected to facilitate the school in provide school information and the public can view school information anywhere without waiting for the school to socialize directly.